Minat Siswa Terhadap Pembelajaran Renang di SMA 1 Teluk Jambe Timur Karawang - Edgar Salvador Dacosta Raja; Febi Kurniawan; Abdul Salam Hidayat (Jurnal Ilmiah Wahana Pendidikan, 2023)
In this study, the problem raised was how class X students' interest in swimming was. The purpose of this study was to determine the interest in swimming in Class X students of SMA 1 TELUK JAMBE TIMUR. The population in this study were students of Class X SMA 1 TELUK JAMBE TIMUR. with a total of 210 students, and the sample used in this study was 210 students, namely the total sampling technique. The variable in this study is the interest of Class X students of SMA 1 TELUK JAMBE TIMUR. for swimming. This study uses a survey method with data collection using a questionnaire. Data analysis used in this study is percentage descriptive statistics. The results showed that the interest of Class X students of SMA 1 TELUK JAMBE TIMUR. towards the sport of swimming which had very high interest as many as 2 students or 0.95%, as many as 98 students or 46.67% had high interest, as many as 87 students or 41.43% had low interest, and as many as 23 students or 10, 95% have very low interest. Based on the results of the study it was concluded that the interest of Class X students of SMA 1 TELUK JAMBE TIMUR. towards the sport of swimming basically has a high interest that is proven that as many as 98 students or 46.67%. The high interest in swimming for Class X SMA 1 TELUK JAMBE TIMUR students. influenced by two things; the first is intrinsic motivation of 58.54%, the second is the extrinsic motivation factor of 52.49%. From the results of this study it is suggested to parents to motivate children and facilitate them to diligently participate in swimming sports at school so they can develop their talents, students should be able to add insight through print or electronic media about swimming sports, to teachers to maintain a good way of teaching. It was fun, because this method of teaching proved to be liked by students, while it was suggested to the school that swimming should be made an extracurricular activity so that it could stimulate interest and direct students' talents towards swimming